Elevated Expression of NOTCH1 Associates with Lymph Node Metastasis of Gastric Cancer and Knock-Down of NOTCH1 Attenuates Tumor Cell Progression - Huang, Bo (Med Sci Monit, 2019)
BACKGROUND: Gastric cancer is the third leading cause of cancer-related death, while its molecular mechanism has not been fully clarified. This study aims to explore the role of Notch signaling in the pathogenesis of gastric cancer. MATERIAL/METHODS: A total of 64 patients with gastric cancer were enrolled. The expressions of NOTCH1 in tumor tissues and adjacent non-tumor tissues were detected by immunohistochemistry staining. The correlation between NOTCH1 expression and clinicopathological features of patients was analyzed. NOTCH1 was knocked down in gastric cancer cells. The effects of NOTCH1 blockade on cell proliferation, migration and cell cycle distribution were analyzed. The expressions of ERK1/2 and phospho-ERK1/2 (p-ERK1/2) were detected using western blotting. RESULTS: Gastric cancer tissues expressed higher level of NOTCH1 than adjacent non-tumor tissues (P<0.05). The high level of NOTCH1 was found to be correlated with gender (male) and lymph node metastasis. However, the expression level of NOTCH1 did not affect the overall survival of patients with gastric cancer. NOTCH1 knock-down repressed the migration and proliferation of gastric cancer cells. Moreover, the cell cycle was arrested at G0/G1 phase by NOTCH1 blockade. The expressions of ERK1/2 and p-ERK1/2 decreased with NOTCH1 knock-down. Further inhibition of ERK1/2 signaling by a MEK1/2 inhibitor U0126 reduced the proliferation of AGS cells, which aggravated the inhibition effect of NOTCH1 knock-down on cell proliferation. CONCLUSIONS: NOTCH1 may play an oncogenic role in gastric cancer. Inhibition of NOTCH1 can efficiently attenuate gastric cancer cell progression, probably in part through cross-talking with ERK1/2 signaling pathway.